Digital Platform Quality and Public Trust as Determinants of Citizen E-Participation in Government Policy Formation - Hanik; Sri Rejeki; Isnaini; Muhammad Hafeez; Noel Jimbai Balang (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The acceleration of the implementation of the Electronic Based Government System (SPBE) still shows an imbalance between the availability of digital infrastructure and the level of public participation in the public policy formulation process. Although the government has provided various digital platforms, their utilisation has not been optimal because public trust in government transparency and accountability has not been adequately established. This study aims to analyse the influence of digital platform quality and public trust on citizen e-participation in government policy formation. This study uses a mixed method with a quantitative approach through the distribution of questionnaires to 73 respondents in West Lombok Regency and Mataram City. The qualitative approach was conducted through in depth interviews with people who had filed complaints and public policy experts. The results show that the quality of digital platforms and public trust simultaneously influence citizen e-participation by 49.9%. Qualitative findings reinforce quantitative results that digital participation is more influenced by public perceptions of government transparency, responsiveness, and accountability than by technical aspects of the platform. This study confirms that the successful implementation of the Electronic-Based Government System (SPBE) depends not only on technological modernisation, but also on building social trust and inclusive and sustainable community involvement as part of strengthening digital governance in Indonesia.